Analysis Posture Work For Reduce Risk of Musculoskeletal Disorders (MSDs) With REBA Method in Wooden Ship Manufacturing Industry - Septa Prastiya Abidin; Lukman Handoko; Indri Santiasih (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
In the current industrial era, work intensity will increase along with consumer demand. As a result, the workload received by workers must be considered, regardless of whether it is a low, medium, or high workload. The focus of this study is on the workload borne by workers who work in the wooden ship manufacturing industry at a company that produces wood as the main material for making wooden ships. Lifting, cutting, and assembling are jobs that are often done in the production section, which require many repetitions and long times. Therefore, it can be concluded that these activities have a very high risk and have a dangerous impact on workers to experience muscle or bone injuries. The Nordic Body Map (NBM) questionnaire was used to conduct an initial measurement of the workload risk received by workers to determine the risk of workload received. The results showed a high value for complaints of Musculoskeletal Disorders (MSDs). Furthermore, further measurements of ergonomic risks were carried out using the Rapid Entire Body Assessment (REBA) method , so that design steps can be taken to improve work posture using the CATIA application to reduce the level of complaints that occur.